2017
DOI: 10.5812/mejrh.45262
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Prevalence of Low Back Pain in Nigeria

Abstract: Context: Low back pain (LBP) is a common musculoskeletal disorder affecting the general population. The prevalence of LBP varies across the studied populations, geographic areas, and age groups.Evidence Acquisition: Prevalence of LBP in Nigeria is largely occupational based. The prevalence differs based on the type of occupation, population, or age group. Therefore, it is necessary to collect data that can help to identify a point or annual prevalence that guides practice and policy making. The databases of Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
0
18
4
Order By: Relevance
“…The annual LBP prevalence rates of 33%–74% estimated in Nigeria ( Bello and Bello, 2017 ) is higher than the prevalence rates of 14%–51% reported in other African countries ( Louw et al, 2007 ). The burden, however, seems to be greater among rural dwellers than urban dwellers as the prevalence rates of 40%–74% ( Omokhodion, 2002 ; Tella et al, 2013 ) found in rural Nigeria is higher than the 44% rate found in urban Nigeria ( Omokhodion, 2004 ).…”
Section: Introductionmentioning
confidence: 59%
“…The annual LBP prevalence rates of 33%–74% estimated in Nigeria ( Bello and Bello, 2017 ) is higher than the prevalence rates of 14%–51% reported in other African countries ( Louw et al, 2007 ). The burden, however, seems to be greater among rural dwellers than urban dwellers as the prevalence rates of 40%–74% ( Omokhodion, 2002 ; Tella et al, 2013 ) found in rural Nigeria is higher than the 44% rate found in urban Nigeria ( Omokhodion, 2004 ).…”
Section: Introductionmentioning
confidence: 59%
“…The one-year prevalence of LBP (57%) among Africans 7 is much higher than the global annual LBP prevalence (39%) 2 . The prevalence rate of 33–74% reported for Nigerians 8 is higher than the 14–51% reported for other African nations 9 and also among the Western nations (20–56%) 10 . Moreover, the one-year prevalence rate ranging between 40% and 74%11, 12 in rural Nigeria is considerably greater than the range 38–44% reported for urban areas 13, 14.…”
Section: Introductionmentioning
confidence: 92%
“…Chronic LBP appears to be a major cause of disability in Nigeria with an estimated annual prevalence of 33-74% [49]. The burden, however, is unduly greater in rural areas compared to urban areas as the oneyear prevalence rate of 74% found in rural Nigeria is higher than the 44% found in urban Nigeria [50,51].…”
Section: Introductionmentioning
confidence: 96%